Polystyrene microplastics cause cardiac fibrosis by activating Wnt/β-catenin signaling pathway and promoting cardiomyocyte apoptosis in rats. (October 2020) - Li, Zekang; Zhu, Shuxiang; Liu, Qian; Wei, Jialiu; Jin, Yinchuan; Wang, Xifeng; Zhang, Lianshuang
Abstract: Microplastics (MPs) are new persistent organic pollutants derived from the degradation of plastics. They can accumulate along the food chain and enter the human body through oral administration, inhalation and dermal exposure. To identify the impact of Polystyrene (PS) MPs on the cardiovascular system and the underlying toxicological mechanism, 32 male Wister rats were divided into control group and three model groups, which were exposed to 0.5 μm PS MPs at 0.5, 5 and 50 mg/L for 90 days. Our results suggested that PS MPs exposure increased Troponin I and creatine kinase-MB (CK-MB) levels in serum, resulted in structure damage and apoptosis of myocardium, and led to collagen proliferation of heart. Moreover, PS MPs could induce oxidative stress and thus activate fibrosis-related Wnt/β-catenin signaling pathway. These results suggested that PS MPs could lead to cardiovascular toxicity by inducing cardiac fibrosis via activating Wnt/β-catenin pathway and myocardium apoptosis triggered by oxidative stress. The present study provided some novelty evidence to elucidate the potential mechanism of cardiovascular toxicity induced by PS MPs. Graphical abstract: Image 1 Highlights: Polystyrene microplastics could cause cardiac fibrosis and dysfunction. Polystyrene microplastics could induce oxidative stress and apoptosis of myocardium. Polystyrene microplastics lead to cardiac fibrosis via activating Wnt/β-catenin pathway and myocardium apoptosis.